Learning from Experiences with Implementation and Financing of Recovery and Peacebuilding Assessments, 1999–2017 - Quick, Ian D.; Demetriou, Spyros (World Bank, Washington, DC, 2018)
The 2008 Joint Declaration on Post-Crisis Assessments and Recovery Planning envisions a common platform for action for the European Union (EU), the United Nations (UN), and the World Bank. The most prominent result was a shared methodology for post-disaster needs assessments (PDNAs) and post-conflict needs assessments (PCNAs), the latter of which has evolved over time into the present approach to recovery and peacebuilding assessments (RPBAs). The most recent review of this experience, completed in 2016 (Garrasi and Allen 2016), concluded that the host governments and the three partner institutions had not consistently followed up their assessments with coherent action. The goal of this review was effectively to identify lessons learned on what works for implementation and financing. This paper is arranged as follows: Section 2 discusses on How to assess the effectiveness and appropriateness of implementation and financing arrangements; Section 3 explains the contextual variables that shape what works, where, and why, drawing upon variations between the case study countries; and Section 4 gives the options and potential approaches for the RPBA process, governance and coordination, institutional alignment and financing.